2004
DOI: 10.1254/jphs.95.124
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin Contributes to the Enhancing Effect of Adenosine on Nerve Growth Factor-Induced Neurite Outgrowth via the Decreased Duration of p38 Mitogen-Activated Protein Kinase Phosphorylation

Abstract: Abstract. Adenosine enhances nerve growth factor (NGF)-induced neurite outgrowth in PC12 cells. We found that adenosine increases NGF-induced phosphorylation of extracellular signalregulated kinase (ERK), but decreases the duration of phosphorylation of p38 mitogen-activated protein (MAP) kinase. Therefore, we further examined the involvement of protein phosphatase in these effects of adenosine. FK506, a specific calcineurin inhibitor, inhibited the enhancing effect of adenosine on the NGF-induced neurite outg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…To determine whether purine nucleosides may attenuate hypoxic cell death, cells were exposed to hypoxia in the presence of adenosine and inosine. In agreement with results by others (Huffaker et al 1984;Braumann et al 1986;Gysbers and Rathbone 1996;Kobayashi and Millhorn 1999;Muroi et al 2004;Ribeiro 2005;Tomaselli et al 2005b), the data presented here demonstrate that adenosine and inosine efficiently rescue the viability of hypoxic PC12 cells and primary cerebellar granule neurons. Earlier data suggested that the effects of adenosine were apparently the result of its conversion to inosine by (a)…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…To determine whether purine nucleosides may attenuate hypoxic cell death, cells were exposed to hypoxia in the presence of adenosine and inosine. In agreement with results by others (Huffaker et al 1984;Braumann et al 1986;Gysbers and Rathbone 1996;Kobayashi and Millhorn 1999;Muroi et al 2004;Ribeiro 2005;Tomaselli et al 2005b), the data presented here demonstrate that adenosine and inosine efficiently rescue the viability of hypoxic PC12 cells and primary cerebellar granule neurons. Earlier data suggested that the effects of adenosine were apparently the result of its conversion to inosine by (a)…”
Section: Discussionsupporting
confidence: 93%
“…1984; Braumann et al. 1986; Gysbers and Rathbone 1996; Kobayashi and Millhorn 1999; Muroi et al. 2004; Ribeiro 2005; Tomaselli et al.…”
Section: Discussionmentioning
confidence: 99%
“…The p38 MAP kinase pathway is also critically involved in NGFinduced neuronal differentiation of PC12 cells. [59][60][61][62] In our current study, p38 MAP kinase pathway was not involved in DA-9801-induced neurite outgrowth in PC12 cells (Fig. 4D).…”
Section: )mentioning
confidence: 43%
“…While the phosphorylation of p38MAPK is necessary for neural differentiation [27, 28], the phosphorylation of p38MAPK inhibits this process [29]. Thus, the results above suggested that the phosphorylation of p38MAPK could promote or inhibit neurite outgrowth depending on the experimental conditions.…”
Section: Discussionmentioning
confidence: 99%